1996
DOI: 10.1037/0022-3514.71.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the impact of counterstereotypic information: Dispositional attributions for deviance.

Abstract: Counterstereotypic behavior by a single out-group member often fails to change out-group stereotypes because it can be dismissed as an exception to the rule. The impact of the "exception" can be strengthened by making the exception appear to be a typical out-group member and by encouraging a dispositional attribution for the exception's' counterstereotypic behavior. These hypotheses were supported in 3 experiments using both artificial and real social categories and both positive and negative stereotypes. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 37 publications
4
43
0
2
Order By: Relevance
“…HamburgerÕs (1994) prediction seems inconsistent with the work of many researchers who exposed participants to one disconfirming group member and found generalization using measures of group stereotypicality (see Garcia-Marques & Mackie, 1999, Experiment 2;Johnston, Bristow, & Love, 2000, Experiments 2 and 3; Kunda & Oleson, 1997;Nisbett, Kranz, Jepson, & Kunda, 1983, Experiment 2;Park & Hastie, 1987;Quattrone & Jones, 1980;Rothbart & Lewis, 1988, Experiment 3;Stapel & Koomen, 1998, Experiment 1;Wilder, Simon, & Faith, 1996;Yzerbyt, Coull, & Rocher, 1999, Experiments 1 and 3). We believe, however, that this inconsistency is more apparent than real.…”
Section: Previous One-member Generalization Experimentsmentioning
confidence: 91%
“…HamburgerÕs (1994) prediction seems inconsistent with the work of many researchers who exposed participants to one disconfirming group member and found generalization using measures of group stereotypicality (see Garcia-Marques & Mackie, 1999, Experiment 2;Johnston, Bristow, & Love, 2000, Experiments 2 and 3; Kunda & Oleson, 1997;Nisbett, Kranz, Jepson, & Kunda, 1983, Experiment 2;Park & Hastie, 1987;Quattrone & Jones, 1980;Rothbart & Lewis, 1988, Experiment 3;Stapel & Koomen, 1998, Experiment 1;Wilder, Simon, & Faith, 1996;Yzerbyt, Coull, & Rocher, 1999, Experiments 1 and 3). We believe, however, that this inconsistency is more apparent than real.…”
Section: Previous One-member Generalization Experimentsmentioning
confidence: 91%
“…When perceivers believe an individual possesses a certain trait, they engage in a one-sided search for confirmatory information, thereby bolstering their initial beliefs (Zuckerman, Knee, Hodgins, & Miyake, 1995). Even in the face of contradictory evidence, stereotype-driven attributions serve to maintain a social perceiver's initial beliefs about a group (Hastie, 1984;Hilton, Fein, & Miller, 1993;Wilder, Simon, & Myles, 1996). For example, people are less likely to use positive traits to explain the success of a member of a negatively stereotyped group (Karpinski & von Hippel, 1996;Maass, Zabbini, & Stahlberg, 1995;Schnake & Ruscher, 1998;Wigboldus, Semin, & Spears, 2000).…”
Section: Stereotypes and Ability Attributions For Test Performancementioning
confidence: 93%
“…As with the case of EC, however, it is important to note that such changes in evaluative judgments do not reflect a direct influence of context stimuli on evaluative judgments. Rather, such influences should also be mediated by associative evaluations.Evidence for explicit attitude changes resulting from differences in pattern activation comes from studies showing that recently encountered members of a social group influence judgments about the group in general (e.g., Bless, Schwarz, Bodenhausen, & Thiel, 700 GAWRONSKI AND BODENHAUSEN 2001;Bodenhausen, Schwarz, Bless, & Wänke, 1995;Gawronski, Bodenhausen, & Banse, 2005;Henderson-King & Nisbett, 1996;Sia, Lord, Blessum, Thomas, & Lepper, 1999;Wilder, Simon, & Faith, 1996). From a general perspective, this research has demonstrated that participants evaluated a social group more negatively when they had recently encountered a negatively evaluated exemplar of the group.…”
mentioning
confidence: 99%